The Inlfuence of External Environment on Balance Score Card-Based Business Performance on Handycraft Msmes in Bandung City - Fitri Leris Febriana Sianturi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This study aims to determine the effect of the external environment on business performance based on a balance score card. The factors tested in this study are the independent variable is the external environment, while the dependent variable is business performance based on a balance score card. The research method used is the verification method. The population in this research is handycraft MSMEs in the city of Bandung, amounting to 392 MSMEs. The sampling technique used is a probability sampling technique with a simple random sampling technique, while to calculate the sample size using the Slovin formula so that the number of samples is 80 MSMEs. The analytical method used is simple linear regression analysis using the SPSS Version 25.00 program. The results showed that the external environment and business performance based on the balance score card were included in the fairly good category. In addition, the results of hypothesis testing show that the external environment has an effect on business performance based on a balance score card on handycraft MSMEs in the city of Bandung. The magnitude of the influence of the external environment in contributing to business performance based on a balance score card is 38.3%.